Sustainable Packaging in Urban Retail: An Assessment of Retailer Awareness in Batasan Hills, Quezon City - Freo, Edmond (International Journal of Sustainability and Advanced Integrated Research, 2026)
High urban consumption patterns continue to generate critical levels of packaging waste, positioning small-scale retailers as vital drivers for local environmental sustainability. This study assessed the level of awareness regarding sustainable packaging and identified the operational barriers to implementation among urban retailers in Barangay Batasan Hills, Quezon City, Philippines. Utilizing a quantitative descriptive research design, data were gathered through purposive sampling from 40 community retailers, predominantly consisting of sari-sari store owners (45%) and mini grocery operators (25%). Data collection employed a structured four-point Likert scale survey evaluating four primary dimensions of awareness alongside perceived structural constraints. The descriptive analysis revealed that while retailers possess a remarkably high environmental consciousness demonstrating a "Strongly Aware" posture toward the environmental impacts of plastic waste (weighted mean = 3.35) their practical application knowledge remains a critical vulnerability. Retailers registered a moderate level of awareness regarding basic sustainable packaging concepts (mean = 3.03) and local policy initiatives (mean = 2.76), but scored lowest on the practical implementation dimension (mean = 2.58), highlighted by a pronounced lack of awareness regarding sustainable material suppliers (mean = 2.40). Financial constraints and market dynamics emerged as the definitive hurdles to behavioral change, with respondents explicitly identifying high premium costs (mean = 3.30) and consumer preference for cheaper alternatives (mean = 3.25) as primary operational barriers. The study concludes that general environmental consciousness does not automatically translate into actual business practices due to restrictive economic pressures and systemic supply gaps. It recommends that Local Government Units shift campaigns toward localized supplier mapping, resource accessibility, and tailored financial incentives for micro-enterprises.